Management of Retained Placenta with Postpartum Hemorrhage in Vaginal Delivery: A Case Report - Dewi Sunarti; Syauqi Kashira YA (The Indonesian Journal of General Medicine, 2026)
Background: Retained placenta is a condition in which the placenta is not delivered or fails to be expelled from the uterus more than 30 minutes after delivery during the third stage of labor, despite active management. This condition can result from inadequate uterine contractions or abnormal placental attachment to the uterine wall. It is a leading cause of postpartum hemorrhage. Postpartum hemorrhage is defined as a condition in which a patient experiences blood loss exceeding 500 mL following delivery, whether via spontaneous vaginal birth or cesarean section. Case Report: A 33-year-old pregnant woman (P3A0) presented with heavy bleeding following a vaginal delivery at the Warungpring Community Health Center (Puskesmas). The patient had undergone a spontaneous delivery at 40 weeks of gestation; the placenta had been delivered, and there appeared to be no retained placental tissue. Three hours after placental delivery, the patient experienced vaginal bleeding amounting to 500 mL, causing weakness and dizziness. Consequently, she was referred to the hospital for further management; dual-line intravenous fluids were initiated at the health center, and urinary catheterization yielded 100 cc of urine. Physical examination revealed vital signs as follows: blood pressure 100/70 mmHg, pulse 80 beats/minute, respiratory rate 21 breaths/minute, and temperature 36°C. Findings included the absence of lacerations, a positive exploration result (suggesting no retained tissue), and anemic conjunctivae. Examinations of the head, nose, ears, mouth, heart, lungs, abdomen, and extremities yielded normal results. Genital examination via inspection of the vulva and vagina revealed fresh red blood flowing from the birth canal. Ancillary testing included a complete blood count, which showed a hemoglobin level of 6.8 g/dL and a leukocyte count of 18,950. The patient received a transfusion of three units of packed red cells (PRC), resulting in post-transfusion hemoglobin and leukocyte levels of 9.6 g/dL and 18,740, respectively. Ultrasonography revealed retained placental tissue within the uterine cavity; consequently, the patient underwent curettage due to retained placenta. A follow-up hemoglobin check after the curettage showed a hemoglobin level of 9.2 g/dL and a leukocyte count of 15,070. Discussion: Retained placenta can occur due to a failure of uterine contractions or inadequate contractions, or because of abnormal placental attachment to the uterine wall. This condition is a cause of postpartum hemorrhage, requiring prompt and appropriate medical intervention to prevent severe complications. From a pathophysiological perspective, retained placenta results from the myometrium's failure to contract optimally at the placental implantation site. Consequently, the placental detachment process is incomplete, leaving blood vessels at the implantation site exposed and leading to hemorrhage. Additionally, abnormalities in placental attachment such as placenta accreta contribute to the risk of retained placenta in pregnant women. Physical examination of patients diagnosed with retained placenta typically reveals an enlarged, soft uterus accompanied by persistent bleeding. If the bleeding is not controlled, signs of hypovolemic shock may develop, such as an increased pulse rate, decreased blood pressure, and pale conjunctiva. These physical examination findings are crucial for determining the immediate course of action. Transabdominal ultrasonography (USG) can be performed to detect any remaining placental tissue within the uterine cavity. Furthermore, ancillary tests including laboratory assessments of hematocrit, hemoglobin, and coagulation parameters are necessary to evaluate blood loss and guide the planning of subsequent management.